CHARACTERISTIC AND MANAGEMENT FOURNIER’S GANGRENE IN ARIFIN ACHMAD REGIONAL GENERAL HOSPITAL OF RIAU PROVINCE - Zamzami, Zuhirman; Jaya, Indra; Yashar, Muhammad Adan; Zalena, Maria (Indonesian Urological Association, 2020)
Objective: To evaluate the characteristic and the management of Fournier’s gangrene. Material & Methods: We reviewed medical records of Fournier’s gangrene patients including age, etiology, invasion of bacteria, underlying disorders, clinical symptom, radiology and laboratory findings, management, and complication in Arifin Achmad General Hospital, Pekanbaru, Riau Province, in January 2012–December 2017. Statistical analysis of univariate was used. Approval of the study was obtained from the Ethical Review Board for Medicine and Health Research, Medical Faculty, University of Riau. Results: There were 19 patients in the study. The result showed that Fournier’s gangrene cases occurred mostly in age 56-65 year old age group in 8 (42.1%) patients. The etiology was from urogenital cause in 15 (78.9%) patients. Most invasion bacteria was Acinetobacter baumannii in 5 (26.3% ) patients. The most underlying disorder was elderly age in 10 (5.6%) patients. The most frequent symptom was puss on the scrotal in 10 (52.6%)patients. The most laboratory examination was puss bacterial culture in 14 (73.7%) patients. The most frequent treatment for Fournier’s gangrene was initial and preoperative management in 19 (100%) patients. The acute complication of Fournier’s gangrene was sepsis in 5 (26.3%) patients. Conclusion: Fournier’s gangrene occurred mostly in elderly age in which Acinetobacter baumannii was the most invasion bacteria and sepsis was the most complication.